Insufficiently Competitive Population Groups in the Labour Market: The Risk of Unemployment - Chepurko, G.; Novak, I. (Социология: теория, методы, маркетинг, 2017)
Since 2013, Ukrainians have been increasingly at risk of becoming unemployed — due to the ongoing political and economic crisis along with the annexation of the Crimea and armed conflict in the east of the country. Furthermore, Ukraine's striving towards EU membership necessitates introducing and implementing the European employment strategy (EES). The purpose of this research paper is twofold: first, to analyse the risk of becoming unemployed among insufficiently competitive population groups in Ukraine, Poland and 28 EU member countries as a whole; second, using the results of comparative analysis, to formulate the national employment policy priorities in accordance with European requirements.